Promotion of acute‐phase skin wound healing by Pseudomonas aeruginosa C(4)‐HSL - Kanno, Emi (Blackwell Publishing Ltd, 2015)

(untitled) (Int Wound J)
A Pseudomonas aeruginosa quorum‐sensing system, which produces N‐(3‐oxododecanoyl)‐l‐homoserine lactone (3‐oxo‐C(12)‐HSL) and N‐butanoyl‐l‐homoserine lactone (C(4)‐HSL), regulates the virulence factors. In our previous study, 3‐oxo‐C(12)‐HSL, encoded by lasI gene, was shown to promote wound healing. However, the effect of C(4)‐HSL, encoded by rhlI gene, remains to be elucidated. We addressed the effect of C(4)‐HSL on wounds in P. aeruginosa infection. Wounds were created on the backs of Sprague–Dawley SD rats, and P. aeruginosa PAO1 (PAO1) or its rhlI deletion mutant (ΔrhlI) or lasI deletion mutant (ΔlasI) was inoculated onto the wound. Rats were injected intraperitoneally with anti‐C(4)‐HSL antiserum or treated with C(4)‐HSL at the wound surface. PAO1 inoculation led to significant acceleration of wound healing, which was associated with neutrophil infiltration and TNF‐α synthesis. These responses were reversed, except for TNF‐α production, when ΔrhlI was inoculated instead of PAO1 or when rats were co‐treated with PAO1 and anti‐C(4)‐HSL antiserum. In contrast, the healing process and neutrophil infiltration, but not TNF‐α synthesis, were accelerated when C(4)‐HSL was administered in the absence of PAO1. This acceleration was not affected by anti‐TNF‐α antibody. These results suggest that C(4)‐HSL may be involved in the acceleration of acute wound healing in P. aeruginosa infection by modifying the neutrophilic inflammation.